Internal PKR crisis in S'gor gets more serious with no solution in sight - Daily Express, (KK) (Sabah Publishing House Sdn. Bhd., 2014)
KUALA LUMPUR: The internal PKR crisis regarding the post of the Selangor Menteri Besar held by Tan Sri Abdul Khalid Ibrahim is actually becoming more serious with no amicable solution in sight.